2011
DOI: 10.1142/s1793604711002160
|View full text |Cite
|
Sign up to set email alerts
|

LiFe1-xMnxPO4/C COMPOSITE AS CATHODE MATERIAL FOR LITHIUM ION BATTERY

Abstract: LiFe 1-x Mn x PO 4/ C composites were prepared as cathode material for lithium ion battery via solid-state reaction and using glucose as reducing agent and carbon source. The crystal structure and morphology were investigated by X-ray diffraction (XRD), scanning electron microscope (SEM) and transmission electron microscope (TEM). The resultant samples were pure olivine compounds with an orthorhombic structure. Their electrochemical performance was studied by galvanostatic charge–discharge test and cyclic volt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Similar scenario was reported by Huang et al, who found that Mn doping could remarkably reduce the size of Zn 1−x Mn x S nanorods under hydrothermal condition. Kinetically, Mn substitution not only reduces the particle sizes and can enhance lattice conductance, 10,11,19 but also generates larger diffusion channels due to expanded unit cell, resulting in a higher Li diffusitivity. a new couple due to Mn 2+ /Mn 3+ emerges at 4.35/4.04 V. It is worth noting that the peaks from LiCo 0.5 Mn 0.5 PO 4 are more symmetric in shape and higher in intensity than those from the pure cobalt compound, manifesting better kinetics and reversibility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar scenario was reported by Huang et al, who found that Mn doping could remarkably reduce the size of Zn 1−x Mn x S nanorods under hydrothermal condition. Kinetically, Mn substitution not only reduces the particle sizes and can enhance lattice conductance, 10,11,19 but also generates larger diffusion channels due to expanded unit cell, resulting in a higher Li diffusitivity. a new couple due to Mn 2+ /Mn 3+ emerges at 4.35/4.04 V. It is worth noting that the peaks from LiCo 0.5 Mn 0.5 PO 4 are more symmetric in shape and higher in intensity than those from the pure cobalt compound, manifesting better kinetics and reversibility.…”
Section: Resultsmentioning
confidence: 99%
“…1 Among them, LiCoPO 4 has recently received peculiar attention due to its high redox potential of 4.8 V (vs. Li + /Li, unless otherwise stated) and thus high energy density of 800 Wh kg −1 , which is essential for batteries to be used in compact energy storage systems. [6][7][8][9][10] Particularly, substitution of electrochemically active cations (Fe 2+ , Mn 2+ , etc.) [2][3][4][5] Various strategies have been developed to improve the electrochemical activity of LiCoPO 4 , including carbon coating, size reducing, and substitution of exotic ions.…”
mentioning
confidence: 99%